Cities for or against citizens? Socio-spatial restructuring of low-income neighbourhoods and the paradox of citizen participation - Perez Rendon, Gabriela (A+BE | Architecture and the Built Environment, 2018)
Urban renewal has evolved into an ambitious and sophisticated urban strategy, recognised as urban revitalisation in America and urban regeneration in Western Europe. This new urban strategy, which tends to be area-based and state-sponsored, claims for the most part to coordinate a wide range of resources, partners and public agencies to bring about social, economic and spatial improvements in underdeveloped and impoverished city areas while improving the livelihoods of the local residents. However, as this study asserts, the objectives behind this new urban strategy have considered, for the most part, the interests of those formulating and implementing such efforts rather than local residents and stakeholders, and produced in turn ‘attractive’ neighbourhoods increasing city revenues, boosting real estate prices, attracting new investments and alluring new residents. Most importantly, citizen participation and gentrification have been concurrently promoted in urban restructuring policy and programmes bringing about a paradox. Citizens have been devised as both subjects and objects of governance (Uitermark, 2014). Urban restructuring programmes have called for residents’ involvement in decision making frameworks while imposing urban revitalisation and regeneration approaches guiding the fate of their neighbourhoods and putting communities at risk of displacement. This study uses comparative research to investigate the way that urban renewal targeting low-income neighbourhoods has evolved into a new urban strategy involving principles and tactics ingrained in neoliberal economic principles. The study shows that this applies in cities led by market-driven development where governments facilitate more than regulate urban growth, and in cities partially exposed to market-driven development and led by interventionist governments which regulate and guide urban restructuring transformations. New York City and The Randstad Holland have been selected as study areas. Above all, the role public policy, instruments and institutional frameworks have played in facilitating citizens’ involvement in decision making in these contrasting contexts is particularly scrutinised looking at two neighbourhoods in the municipalities of Brooklyn and Rotterdam; Bushwick and Tarwewijk, respectively. The study exposes the motives, successes and drawbacks of public programmes and instruments fostering citizen participation and community-led change, in an effort to both create awareness of potential risks in the case of unsuccessful initiatives, and envision the exchange and adaptation of some of those successful schemes for the production of more equitable neighbourhoods. This thesis asks to what extent urban restructuring trends converge in the two contrasting geographical areas since both territories have been exposed to the same global agents and influences that have impacted urban restructuring policy and interventions (i.e. neoliberal economic policies, global financing, interurban competition, etc). However, it recognizes that the outcomes may manifest differently due to differences in welfare programmes, urban policy, implementation frameworks, local and global housing markets at the neighbourhood level, as well as variations in local governance structures and instruments facilitating civic participation in urban and housing restructuring programmes. Citizen participation in urban restructuring in America and Western Europe Citizen participation was widely recognised in urban and housing public programmes in America and Western Europe during the 1960s and 1970s. In a time of political and economic shifts and as a result of citizen struggles and social movements, the democratisation of decision making in planning became a political act. Feeling alienated from the urban transformations taking place in their own neighbourhoods, citizens organised and demanded to be part of the production of cities. Citizen demands were gradually adopted and institutionalised by public policies and programmes. However, such progressive approaches did not last for long. Citizen participation in urban renewal and housing programmes lost agency as liberal urban policy was gradually overthrown beginning with the recessions of the late 1970s and the conservative governments that followed in the 1980s and beyond. National states and municipalities began withdrawing from those endeavours while coordinating efforts to attract private partners and investment to pursue larger and more ambitious urban restructuring interventions in cities. Certainly, the community-driven scope of a number of public programmes shifted to a more ambitious one that sought to achieve economic growth and profitable urban development bringing about shifts in urban restructuring policy, programmes, funds and leadership over the following decades. Evidently, as neoliberal economic agendas became more and more ingrained in urban policy and programmes guiding urban restructuring, uneven development and segregation became more stark bringing new urban challenges across cities. What is interesting is that in a context of increasing decentralisation, privatisation, and deregulation of urban restructuring interventions that have impacted directly citizens and particularly low-income communities, national states began once again promoting citizen participation. As national states have increasingly devolved decision-making and resources to lower government levels, municipalities and their partners, from the private and not-profit sectors, have been more involved in making and implementing local policies and addressing citizens and community needs. However, the motive, scope, impact and outcome of current local policies and programmes fostering the involvement of low-income and minority groups in urban restructuring programmes have left many questions unresolved. A number of studies assert that the deliberate activation of specific community groups by national states and their partners in urban restructuring programmes has been promoted: (1) to deal with the unprecedented economic and social consequences that emerged out of the neoliberal project through socially interventionist and ameliorative public policies and programmes (Peck & Tickle, 2002; Uitermark, 2014); (2) to control and discipline vulnerable and deprived groups who have been victims of the byproducts of the current neoliberal urbanisation and who should be ‘integrated’ through highly engineered measures (Albers & van Beckhoven, 2010; Brenner, Peck & Theodor 2009; Schickel & van der Berg, 2011; Uitermark, 2014; Uitermark & Duyendak, 2008); and (3) to build coalition politics by assembling strategic alliances in areas undergoing political and socio-spatial restructuring while seeing themselves as symbols of the community to legitimise their powers and in turn assert control and gain support to fulfil ongoing plans without opposition (Harvey, 1989). This study delves into these claims by scrutinising recent urban restructuring approaches in two different geographical contexts and investigating policies and programmes advocating for citizen participation. Research content and questions This study is structured in five sections: (1) introduction (2) theoretical framework; (3) politico-institutional historical context; (4) case study research; and (5) final analysis of comparative research. The first section, Introduction, outlines the research framework of this study including problem statement, aim, methodological approach and selection of case studies as well as the design and structure of this research. The second section, Cities for or against Citizens, includes Chapter 2 which provides a theoretical understanding of the way urban restructuring discourses, objectives and strategies have evolved in America and Western Europe. It introduces the right to the city as one of the main demands citizens, academics, activists, advocate planners, civic and grassroots groups have called for, and mobilised around, to fight the injustices produced by contemporary neoliberal urbanisation. It then explains the way that economic restructuring has led to new socio-spatial configurations and politicoeconomic relations in cities with impactful outcomes, such as uneven development and segregation and new institutional policy and governance frameworks. In relation to such new developments, the shift of urban renewal into a more ambitious and coordinated global and economic strategy is presented in conclusion to section two, enquiring about the state’s continuous promotion of participation and integration of citizens in urban restructuring policies and programmes targeting low-income neighbourhoods in both geographical areas. The third section, The Evolution of Urban Restructuring, provides the politicoinstitutional historical context of urban restructuring in New York City and the Randstad Holland. It encompasses Chapter 3 and 4 which carefully explain public policy, programmes and instruments involving or facilitating citizen participation in urban restructuring and housing programmes in low-income neighbourhoods from the postwar years until today. Chapter 3 focuses on policies and programmes bringing about urban restructuring in New York City, from the urban renewal programmes calling for 'citizen participation ’for the first time and the War on Poverty programmes which institutionalised the 'widespread participation of the poor' for the improvement of deprived inner city areas, to the tenant-led sweat equity housing management programmes that emerged after the city’s nadir of the 1970s, and the public policies and instruments of devolution which gave way to the professionalisation of grassroots movements, and in turn, the growth of the non-profit sector currently in charge of community and housing development. On the other hand, Chapter 4 explains the evolution of social oriented policies and participatory programmes promoted for the restructuring of low-income neighbourhoods in the Randstad Holland, from community work [opbouwwerk] with specific goals and targets and Building for the Neighbourhood [Bouwen voor de Buurt ], a collective and politicised urban renewal effort bringing about political and social change, to more recent policy programmes promoting the integration and participation of low-income and marginalised communities. The historical account of these two chapters provides an overview of the endeavours national states have undertaken at different levels facilitating citizen participation and community-led initiatives, as well as their successes and shortcomings. Both chapters offer a policy context useful for the analysis of the most recent urban restructuring frameworks and trends, which are examined in the following chapters. The ultimate objective of this section is to answer the following question: How have public policy and programmes targeting low-income and minority districts evolved with the decentralisation of national state’s power and resources? The fourth section, Socio-spatial Restructuring in Low Income Neighbourhoods in New York City and the Randstad Holland, involves case study research. Composed of Chapter 5 and 6, it delves into the socio-spatial restructuring of two lowincome neighbourhoods in New York City and the Randstad Holland; Bushwick and Tarwewijk, respectively. The way urban restructuring policies and programmes depicted in the previous two chapters have evolved and transformed socio-spatial configurations through shifts in housing provision —including planning, funding and development schemes— and local urban governance are illustrated in detail. Above all, policies, programmes and local initiatives promoting the involvement of citizens in decision making processes are particularly examined. Additionally, the role of local stakeholders in the implementation of those policy frameworks is presented considering decentralisation, privatisation and deregulation trends in housing and urban restructuring. Lastly, a critical analysis of the purpose, evolution and outcomes of public policies, planning strategies, participatory endeavours and trends facilitating the restructuring of low-income income neighbourhoods is offered. The central questions in this section are the following: How have changes in public policy and programmes played out in cities with liberal governments and unregulated market-driven development and in cities with interventionist governments and regulated market driven developments? How and why have national states promoted the integration and participation of residents of low-income and minority groups throughout the evolution of urban restructuring processes? The last section, The New State-Led Urban Restructuring Strategy: Analysis and Alternatives, offers a final analysis and a reflection on the comparative research. It is composed of Chapter 7 and 8. Chapter 7 provides a summative analysis of the previous chapters by delving into the way urban revitalisation and regeneration in low-income neighbourhoods in America and Western Europe, respectively, have evolved into a new urban restructuring strategy with clear objectives, locations, and approaches. The urban restructuring trends outlined in this section depict current state-sponsored policies, strategies, tools and measures promoted in disinvested areas to integrate these segregated sites into the new economic functions of cities. Additionally, it lays out the way citizens have been concurrently perceived by policy and public programmes as part of the new urban restructuring strategy. This section concludes with Chapter 8 which reflects on the rise of urban mobilisations and counteracting urban practices responding to the increasing disability of citizens to be part of the transformation of their own living environments. This last section aims to answer the main question of this investigation: Are cities being restructured for the welfare of citizens or are they being reshaped against the will, needs and interests of their own citizens? Urban restructuring trends and alternatives The final analysis of the study, as it was mentioned above, lays out the current directions of urban restructuring that are identified, while examining the evolution of urban restructuring policies, programmes, and strategies of implementation targeting low-income neighbourhoods in New York City and the Randstad Holland. As part of the findings of this study, the following urban restructuring trends were identified: (1) urban restructuring being used by national states as an instrument for speculation, competitiveness and economic growth; (2) an increasing outward diffusion of urban restructuring from urban centres to peripheral areas; (3) a rise of area-base policies, investments and urban interventions; (4) ‘social mixing’ as urban policy to diversify housing opportunities and in turn promote socially and economic diverse neighbourhoods; (5) a generalisation of state-led gentrification in urban restructuring policy and programmes; (6) new regulatory policy and institutional configurations; (7) the waning of housing provision for the poor and the working-class; and lastly, and most importantly for this study, (8) citizen participation being devised as a state instrument for the pacification, control and bargaining of low-income neighbourhoods in transformation. These trends certainly bring to light the fate of low-income communities and neighbourhoods, but also underscore the fields and spaces— from policy, programmes and governance frameworks to urban and housing planning approaches —where intervention is needed to generate more equitable neighbourhoods. Against this background, and concluding the final analysis, this study also highlights successful approaches and practices facilitating citizen- and community-lead urban restructuring processes in New York City and the Randstad Holland. Historically, as this study shows, progressive policies have promoted and, in many cases, managed to create democratic tools and processes of planning and development, particularly in times of crisis and when the private sector is not willing nor able to intervene. Such policies and their outcomes have proven, even with their shortcomings, that cities for citizens can be produced with a fair distribution of political power, resources and benefits. Alternative forms and models of housing development which have been devised, for the most part, by common citizens responding to the urgency of both creating housing according to their own needs and priorities and producing less alienated dwelling environments are underscored including housing cooperatives, community land trusts, self-management housing programs and other nonspeculative and regulated housing development schemes. Interestingly, just as the policy and planning approaches of the two case studies tend to converge, so do the principles and purpose of the urban restructuring models in many ways. But the effects manifest themselves differently due to the differences in institutional policy and government frameworks in each context. These schemes have been presented throughout this study but are particularly emphasised at the end of this study since they offer a valuable insight into alternative ways of restructuring low-income neighbourhoods, and urban districts in general, so as to produce more equitable cities, in other words—cities for citizens.